2001
DOI: 10.1264/jsme2.2001.125
|View full text |Cite
|
Sign up to set email alerts
|

Silicified Microbial Community at Steep Cone Hot Spring, Yellowstone National Park.

Abstract: At Steep Cone hot spring, Lower Geyser Basin, Yellowstone National Park, a mound of siliceous deposits called "siliceous sinter" forms from discharged boiling geothermal water that is supersaturated with amorphous silica. Electron-probe microanalyzer (EPMA) observations suggested that silica is deposited on the surface of the cells and that microorganisms affect the formation of the siliceous sinter. EPMA signals and backscattered electron images of sinter samples taken at the inner wall of the boiling pool re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…Bacteria within Thermus are always the predominant microbial components in terrestrial hot springs all over the world [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria within Thermus are always the predominant microbial components in terrestrial hot springs all over the world [9] .…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that the remnnnt cesium remained in the cells of microorganisms. Bacteria within the genus Thermus are always the predominant microbial species in terrestrial hot springs all over the world [9,10] . Thermophilic cyanobacteria have been verified as responsible for initiating siliceous precipitation both in situ and under controlled laboratory conditions [11,12] .…”
mentioning
confidence: 99%
“…Scanning electron microscopy and electron probe microanalysis Cell aggregates on the glass surface of culture bottles were examined using a JEOL JCXA-733 electron microprobe analyzer (JEOL Ltd., Tokyo, Japan) to identify silicon and other metallic minerals (relative qualitative analysis) (Inagaki et al, 2001).…”
Section: Turbidity Measurementmentioning
confidence: 99%
“…We previously observed numerous bacteria within the silica scale at a geothermal power plant, and after examining their population and its characteristics, we suggested that it is the extremely thermophilic bacteria that participate in forming the siliceous deposits (Inagaki et al, 1997(Inagaki et al, , 1998(Inagaki et al, , 2001. One of these bacteria, Thermus thermophilus TMY, was isolated from the silica scale (Fujino et al, 2008) and was found to induce precipitation of supersaturated amorphous silica (4400 p.p.m SiO 2 ) during its log-growth phase (Inagaki et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, when that geothermal water is discharged to the surface, the silicic acid concentration becomes supersaturated as the water boils, frequently leading to the formation of siliceous deposits called "silica sinter" (11). Microscopic observation of such siliceous deposits reveals many microbe-like structures (20), and it has been suggested that these fossils represent archean microorganisms that grew in the hot, supersaturated fluids (26). There have been a number of experimental studies carried out with the aim of characterizing the physical changes associated with various bacteria during silicification (23,26,31,33,37); however, the effect of silica on the bacterial habitat in geothermal environments and the mechanism by which siliceous deposits are formed remain unexplained.…”
mentioning
confidence: 99%